2004
DOI: 10.1055/s-2004-836127
|View full text |Cite
|
Sign up to set email alerts
|

Flap Prefabrication and Prelamination with Tissue-Engineered Cartilage

Abstract: In reconstructive surgery, the integration of tissue-engineered cartilage in a prefabricated free flap may make it possible to generate flaps combining a variety of tissue components, to meet the special requirements of particular defects. One aim of the present study was to investigate prefabrication of a microvascular free flap by implanting a vessel loop under a skin flap in a rabbit model. A second aim was to report on the authors' preliminary experiences in prelaminating prefabricated flaps with autologou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…The mouse model presented here works with the combination of a flow-through model with later transposition of the construct to confirm the sole dependence of the vascularized construct on the implanted vessels and to answer questions concerning transposition or perform pre-studies prior to free microsurgical transfer in rats or rabbits. According to the findings of Staudenmaier et al (2004) and Nguyen et al (2005), we performed a transposition after 3 weeks with vascularization being sufficient after this time. This is also consistent with the practice of other investigators who have described sufficient vascularization after 3 weeks (Takato et al 1993;Itoh 1992).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The mouse model presented here works with the combination of a flow-through model with later transposition of the construct to confirm the sole dependence of the vascularized construct on the implanted vessels and to answer questions concerning transposition or perform pre-studies prior to free microsurgical transfer in rats or rabbits. According to the findings of Staudenmaier et al (2004) and Nguyen et al (2005), we performed a transposition after 3 weeks with vascularization being sufficient after this time. This is also consistent with the practice of other investigators who have described sufficient vascularization after 3 weeks (Takato et al 1993;Itoh 1992).…”
Section: Discussionmentioning
confidence: 94%
“…Others have introduced rat models to solve problems concerning prefabrication (Tan et al 2004;Tanaka et al 2003). Staudenmaier et al (2004) and Hoang et al (2005b) demonstrated in a rabbit model that flaps could be well vascularized by an arteriovenous vessel loop. Hoang et al (2009) even simulated a free microsurgical transfer of the prefabricated, prelaminated flaps.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Between the epithelial layer and the hyaline cartilage tissues we can find a submucosal layer of capillary networks. Normal cartilage tissue preventing the in-growth of capillary vessels is separated from other connective tissues (i.e., submucosa) by a fibrous membrane [71,72]. Unlike parenchymal organs, the trachea is supplied with a network of small vessels inaccessible to direct revascularization through vessel anastomosis.…”
Section: Future Perspectivesmentioning
confidence: 99%